Performance Analysis of Multiuser Detection for Multibeam Satellites Under Rain Fading - Arnau, Jesus; C. Mosquera (2012 6th Advanced Satellite Multimedia Systems Conference (ASMS) and 12th Signal Processing for Space Communications Workshop (SPSC) (ASMS/SPSC 2012), 2012)
Multibeam satellite systems are nowadays widely employed, and their use is expected to grow in the next decades. This has raised the interest for signal processing techniques able to mitigate the interference among beams, since they could enable a much more aggressive spectrum reuse. From an engineering point of view, the design of the system must be no longer based on the capabilities provided by the usual physical layer; it should take into account the presence of these interference canceling techniques, predict their performance as accurately as possible -even under a number of impairments and non-idealities- and design accordingly in order to fully exploit them. In this paper, we investigate the effect of a practical impairment of great importance, namely, the attenuation due to the rain, on the performance of a return link which performs MMSE interference canceling. Analytical expressions are derived for a number of performance measures based on the statistical characterization of the rain attenuation.
Keywords: dynacs; hybrid beamforming; multibeam satellites.; Multiuser detection; rain fading; satcom